079 Formulating Guideline Recommendations about Important Clinical Questions with Low or Very Low Quality Evidence: The Case of Opioids for Chronic Pain. (15th August 2013) - Harris, J; Hegmann, K; Weiss, M
Abstract : Background: Deaths from prescription opioids now exceed those from street drugs or motor vehicle injuries in the US. Morbidity in has greatly increased as well. Rapid acceleration of opioid prescription for chronic non-cancer pain (CNCP) began in the mid-1990s with heavy marketing and support by opioid manufacturers. Some current recommendations advocate increased use of opioids despite a lack of quality evidence of long-term efficacy, considerable evidence of harms, and a tenuous understanding of CNCP. Objectives: To review the recommendation methodology used in cases of low quality evidence; to describe the process of recommendation development for opioid use for CNCP Methods: The American College of Occupational and Environmental Medicine updated its systematic reviews and clinical practice guideline for the use of opioids for CNCP using critical appraisal and explicit panel methods. Panels consider population and clinical risk and benefit. Results: Critical appraisal revealed low quality evidence. Most studies and many guideline panellists were funded by pharmaceutical companies. Harms were identified in observational studies. Discussion: Available guidelines tended to make vague recommendations that depended on clinician judgement. This panel therefore used methods to formulate recommendations that protect patients and the public, and a conservative and function-based approach to patient management. Implications for Guideline Developers: Guidelines for areas in which evidence is low quality and the benefit to risk relationship is unclear should exercise caution in making recommendations, provide patient information, and recommend informed consent and careful patient management.